"[T]Hose Who Had Money Were Opposed to Us, and Those Who Were Our Friends Were Not the Moneyed Class": Philadelphia and the 1837–1838 Canadian Rebellions. Issue 1 (2nd January 2017) - Dagenais, Maxime
ABSTRACT: In early January 1838, weeks following a disastrous military defeat at the hands of the British at Saint-Eustache, in the British colony of Lower Canada, two patriotes leaders, Dr. Robert Nelson and Dr. Edmund O'Callaghan, arrived in Philadelphia. Their mission was to find military and financial support among local residents for the 1837 Rebellion. A few days later, they left empty-handed and disappointed. According to O'Callaghan, those who supported them were incapable to help, while those who had the means to offer concrete assistance were, quite simply, opposed to their crusade. Why did Nelson and O'Callaghan leave empty-handed? Were O'Callaghan's assumptions about the people of Philadelphia correct? This article explains why the Patirote mission to Philadelphia failed and suggests that O'Callaghan was incorrect. The mission did not fail because their allies were too poor while those with money opposed them. Instead, though many actually hoped that the rebels succeeded and offered much moral support and encouragement, all were quite simply unwilling to offer any military or financial support, citing American neutrality, economic uncertainty, and the fear of British retaliation.